Effects of the Severe Acute Respiratory Syndrome Coronavirus 2 Inactivated Vaccine on the Outcome of Frozen Embryo Transfers: A Large Scale Clinical Study - Zhang XL; Chen YH; Zhang SP; Wu XQ; Wang XP (Dove Medical Press, 2023)
Xue-Luo Zhang,* Yan-Hua Chen,* Si-Ping Zhang, Xue-Qing Wu, Xian-Ping Wang The Reproductive Center, Children's Hospital of Shanxi and Women Health Center of Shanxi, Shanxi, People's Republic of China*These authors contributed equally to this workCorrespondence: Xian-Ping Wang, The Reproductive Center, Children's Hospital of Shanxi and Women Health Center of Shanxi, 13 Xinmin North Street, Xinghualing District, Taiyuan, Shanxi, 030001, People's Republic of China, Tel +86 13934500073, Email wangxianpingwxp@outlook.comBackground: Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a life-threatening infectious disease that has become a global pandemic.Objective: This study aimed to explore the effects of SARS-CoV-2 inactivated vaccine on the outcome of frozen embryo transfer (FET).Methods: We grouped patients who underwent FET between August 2021 and March 2022 based on their vaccination status, number of doses, and the interval between the last dose and the FET, and then compared the differences in pregnancy outcomes among the groups.Results: There were 1084 vaccinated patients and 1228 non-vaccinated ones. There were significant differences in the live birth rate between the vaccination and non-vaccination groups (16.61% vs 28.26%), among the one-dose, two-dose, and three-dose groups (22.28% vs 19.51% vs 7.27%), and among the groups with interval ≤ 1 month, 1- 2 months, and ≥ 2 months (38.38% vs 27.27% vs 12.03%). There were significant differences in the persistent pregnancy rate between the vaccination and non-vaccination groups (22.88% vs 14.09%), among the one-dose, two-dose, and three-dose groups (14.51% vs 23.80% vs 38.18%), and among the groups with interval ≤ 1 month, 1- 2 months, and ≥ 2 months (1.01% vs 8.44% vs 28.16%). There were significant differences in the neonatal weight between the vaccination and non-vaccination groups [3805.50 (3746.00- 3863.50) vs 2970.00 (2500.00- 3400.00)]. There were significant differences in the premature birth rate among the one-dose, two-dose, and three-dose groups (23.26% vs 34.59% vs 100.00%), and among the groups with interval ≤ 1 month, 1- 2 months, and ≥ 2 months (15.79% vs 21.43% vs 37.00%).Conclusion: Pregnancy outcomes were not affected by taking the SARS-CoV-2 inactivated vaccine before FET, the number of doses, and the interval between doses. These findings provide evidence supporting the safety of administering the SARS-CoV-2 inactivated vaccine during pregnancy, which can be used as a guide for vaccinating patients undergoing ART.Keywords: COVID-19, frozen embryo transfer, pregnancy rate, vaccination